The expansion of international hotel systems (IHS) as a research issue in Polish and foreign academic literature - Janiak, Małgorzata (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
Apart from travel, the hotel industry is the part of tourism that generates the greatest expense for a tourist and this may have many positive implications for local markets (Yin, Hastings, 2007). The modern hotel market is largely controlled by a dozen or so global hotel systems that compete year after year to be the largest player on the market (both in terms of the number of hotels or number of rooms). International hotel systems (IHS) affect the activities of the entire industry in a variety of ways, including entering new markets, shaping trends, implementing innovations in products offered or management methods, adjusting innovations to changes taking place in society and the economy, and responding to the activities of competitors. The aim of the article is to find out the current state of knowledge related to the activities of IHS and to show how important it is to conduct research in this area. In this work, the author used only academic literature (Polish and foreign), without making use of trade materials.